2013
DOI: 10.4028/www.scientific.net/aef.8-9.185
|View full text |Cite
|
Sign up to set email alerts
|

The Optimization of Microgrids Operation through a Heuristic Energy Management Algorithm

Abstract: Abstract. The concept of microgrid was first introduced in 2001 as a solution for reliable integration of distributed generation and for harnessing their multiple advantages. Specific control and energy management systems must be designed for the microgrid operation in order to ensure reliable, secure and economical operation; either in grid-connected or stand-alone operating mode. The problem of energy management in microgrids consists of finding the optimal or near optimal unit commitment and dispatch of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…[19]. In [20] It is suggested to use a heuristic algorithm for stand-alone MG energy management to prevent wasting the available renewable potential at each time interval. The authors of [21] suggested an artificial neural network ANN-based model for the integration of RESs that would minimize costs and limit carbon emissions.…”
Section: Introductionmentioning
confidence: 99%
“…[19]. In [20] It is suggested to use a heuristic algorithm for stand-alone MG energy management to prevent wasting the available renewable potential at each time interval. The authors of [21] suggested an artificial neural network ANN-based model for the integration of RESs that would minimize costs and limit carbon emissions.…”
Section: Introductionmentioning
confidence: 99%
“…A MG's Energy Management System (EMS) could be a sophisticated machine-controlled system largely focused on resource schedule optimization: It can optimize the management of distributed power and energy storage devices within the microgrid thanks to superior information technology. A planning problem's premise is to accurately state load and supply data; a comparative study of wind speed statements is discussed [26].…”
Section: Energy Management Systemsmentioning
confidence: 99%
“…To increase the system reliability and to cover the fluctuations in the generation of the renewable energy sources and the load among the time, the spinning reserve is necessary in the MG and the following constraint should be satisfied [15][16][17][18]20,21,24,25 where R t is the schedule reserve capacity at time (t).…”
Section: Reserve Capacitymentioning
confidence: 99%